Urban waste composting with addition of several phosphorus sources - Peixoto, Ricardo Trippia dos G.; Almeida, Dejair Lopes de; Franco, Avilio Antonio (Pesquisa Agropecuaria Brasileira, 2014)
The composting process of urban waste with several P sources was monitored until maturation of the compost. The experiment was laid out in a randomized block design with four replications and five treatments: a) pure urban waste (UW), b) UW with araxá rock phosphate (UW + ARP), c) UW with patos de minas rock phosphate (UW + PRP), d) UW with ARP and ammonium sulphate (UW + ARF + AS) and UW with triple superphosphate (UW + TS). Heaps with 600 kg of fresh UW were incubated in open field after mixing throughly, according to treatment with 10,6 kg P2O5 and 5,3 kg N per UW ton. The heaps were mixed and the temperature, moisture, pH and C/N ratio were determined many limes during the 91 days of the composting process. At the final sampling, available and total P content were determined. One extraction of P using the exchange resin method showed no increase in available P from ARP or PRP after the composting process. The addition of AS also did not increase the availability of P from ARP. There was no effect of ARP and PRP on the temperature, moisture, pH and C/N ratio during composting, while the TS and AS affected the pH when compared with pure UW.